2011
DOI: 10.1007/s11432-011-4306-8
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous cooperative communication systems: A survey on signal designs

Abstract: Cooperative communications is a promising technique for future high speed wireless communications. These systems may be formulated as virtual multi-input multi-output (MIMO) systems where spatial/cooperetive diversity is a key advantage. However, different from MIMO systems, one of the major challenges for cooperative communications systems is that the cooperative transmissions in cooperative systems may be neither time nor frequency synchronized, since the transmissions are from multiple cooperative nodes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 83 publications
(114 reference statements)
0
17
0
Order By: Relevance
“…2 + LN − 1 is the computational complexity to evaluate the objective function χ in (16). Note that extensive simulations demonstrate that the proposed DE algorithm on average converges to the true estimates after approximately D I = 220 and D I = 530 iterations for K = 2 and K = 4, respectively, for a wide range of SNRs.…”
Section: Ln )K + (Ln )mentioning
confidence: 99%
See 4 more Smart Citations
“…2 + LN − 1 is the computational complexity to evaluate the objective function χ in (16). Note that extensive simulations demonstrate that the proposed DE algorithm on average converges to the true estimates after approximately D I = 220 and D I = 530 iterations for K = 2 and K = 4, respectively, for a wide range of SNRs.…”
Section: Ln )K + (Ln )mentioning
confidence: 99%
“…Remark 2: Even though the general conditions for global convergence of evolutionary algorithms are established in [48], it cannot be analytically shown that DE meets these conditions [49] and converges to the global solution of (16). Moreover, in [48], no specific algorithm that meets these conditions is proposed.…”
Section: B Differential Evolution Based Estimationmentioning
confidence: 99%
See 3 more Smart Citations